The Concept of Balance at Sekati Ririg Gending in Tejakula, Buleleng Regency - Aditya Putra, I Ketut; Santosa, Hendra; Sudirga, I Komang (Harmonia: Journal of Arts Research and Education, 2020)
This study aims to determine the concept of balance found in playing techniques, tempo, and dynamics (ngumbang-ngisep) at Sekati Ririg Cenik gending in Tejakula, Buleleng Regency. The research is focused on the presentation using the barungan of Gong Kebyar gamelan, because at the time of handling the beginning observation, it was presented to accompany religious ceremonies at Pura Maksan Tejakula. This research is a qualitative study using several data collection techniques; observation, interviews, documentation, and literature. The approach used is a musicological approach using aesthetic theory. The results obtained from this study are the concept of dualism balance in terms of some of the forming elements in it, such as playing techniques on instruments pemade, kantilan, trompong, reyong, and ceng-ceng kopyak. These are some of the instruments that use the polos-sangsih system in their playing. Playing Technigue usually play parallel to the tempo, while playing technique sangsih is still playing against the tempo. Furthermore, the concept of balance at tempo can be seen from the speed with which gending Sekati Ririg Cenik is presented. The presentation begins with a slow tempo, then after several repetitions of the gending the tempo slowly changes to faster until it reaches the end of the gending, and the tempo is again set to slow. Likewise with the concept of dynamic balance which can be viewed from the loudness of the musical presentation. Setting the tempo and dynamics is intended to achieve balance and will not cause boredom in the presentation. These three things can be implemented in the Gong Kebyar gamelan instrument which is used as a medium in presenting Sekati Ririg Cenik gending by the community in Tejakula Village.